La perception des changements environnementaux : le cas de la collectivité côtière de Shippagan (Nouveau-Brunswick, Canada) - Vincent Stervinou; Elise Mayrand; Omer Chouinard; Alida NadègeThiombiano (VertigO)
In order to support coastal communities in the process of establishing attenuation and adaptation strategies to environmental changes, it is essential to understand how people perceive these changes. The aim of this study is to verify to what extent people’s perception of environmental changes matches quantitative data computed for the area of interest. Semi-directive interviews were conducted with residents of Shippagan (NB, Canada). A focus group was subsequently organized. Six main topics were discussed : climatic changes, sea level changes, erosion, aquatic pollution, biodiversity and drinking water resources. We also searched databases from government agencies and non government organizations to build time series of environmental variables depicting the aforementioned topics. We were able to gather both local knowledge and quantitative data for eleven variables. The temporal tendencies observed by local people were consistent with quantitative data for six variables. In some of the remaining cases, the apparent discrepancy between the quantitative data and local knowledge might have resulted from the different time frames covered by theses two sources. This correspondence between local knowledge and quantitative environmental data could be translated into incentives for taking concrete actions that would ameliorate the communities’ resilience.